Răspuns :
[tex] \int \frac{ {x}^{2} }{16 - {x}^{6} } \: dx [/tex]
[tex] = \int \frac{ {x}^{2} }{16 - { ( {x}^{3}) }^{2} } \: dx[/tex]
[tex]t = {x}^{3} = > dt = ( {x}^{3}) ' = 3 {x}^{2} \: dx[/tex]
[tex] = \frac{1}{3} \int \frac{ 3{x}^{2} }{16 - {t}^{2} } = \frac{1}{3} \int \frac{dt}{16 - {t}^{2} } [/tex]
[tex] = - \frac{1}{3} \int \frac{dt}{ {t}^{2} - 16} = - \frac{1}{3} \times \frac{1}{2 \times 4} \times ln | \frac{t - 4}{t + 4} | [/tex]
[tex] = - \frac{1}{24} \times ln | \frac{ {x}^{3} - 4}{ {x}^{3} + 4} | [/tex]
[tex] = - \frac{ln | {x}^{3} - 4| - ln | {x}^{3} + 4| }{24} = \frac{ln | {x}^{3} + 4| - ln | {x}^{3} - 4 | }{24} + C[/tex]
[tex] = \int \frac{ {x}^{2} }{16 - { ( {x}^{3}) }^{2} } \: dx[/tex]
[tex]t = {x}^{3} = > dt = ( {x}^{3}) ' = 3 {x}^{2} \: dx[/tex]
[tex] = \frac{1}{3} \int \frac{ 3{x}^{2} }{16 - {t}^{2} } = \frac{1}{3} \int \frac{dt}{16 - {t}^{2} } [/tex]
[tex] = - \frac{1}{3} \int \frac{dt}{ {t}^{2} - 16} = - \frac{1}{3} \times \frac{1}{2 \times 4} \times ln | \frac{t - 4}{t + 4} | [/tex]
[tex] = - \frac{1}{24} \times ln | \frac{ {x}^{3} - 4}{ {x}^{3} + 4} | [/tex]
[tex] = - \frac{ln | {x}^{3} - 4| - ln | {x}^{3} + 4| }{24} = \frac{ln | {x}^{3} + 4| - ln | {x}^{3} - 4 | }{24} + C[/tex]